2017
DOI: 10.1177/1687814017730731
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Reconfigurable B approach for the specification and verification of B-based distributed reconfigurable control systems

Abstract: This research article proposes a novel approach called Distributed Reconfigurable B to specify and verify distributed reconfigurable control systems using B method. Reconfiguration signifies the dynamic adaptation of the system behavior to the evolution of its environment by applying a reconfiguration scenario. A multi-agent architecture is defined to affect a reconfiguration agent to ensure local reconfiguration for each subsystem and a coordination agent to manage the different subsystems to guarantee the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The research reported in [27] extended to [137] and [138] proposes reconfigurable B (R-B) as an extension of B method. The authors apply R-B to a manufacturing production line and apply an improved verification by removing redundant verification of similar operations in different reconfigurable behaviors.…”
Section: Modeling With B Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research reported in [27] extended to [137] and [138] proposes reconfigurable B (R-B) as an extension of B method. The authors apply R-B to a manufacturing production line and apply an improved verification by removing redundant verification of similar operations in different reconfigurable behaviors.…”
Section: Modeling With B Methodsmentioning
confidence: 99%
“…The work reported [34] develops a reconfigurable embedded controller of temperature. The work reported in [138] develops with B method a reconfigurable production line. The work developed in [9] develops reconfigurable platoons.…”
Section: Deployment and Hardware Testmentioning
confidence: 99%